2005
DOI: 10.1029/2005gl022410
|View full text |Cite
|
Sign up to set email alerts
|

How exceptional was the early August 2003 heatwave in France?

Abstract: [1] The summer of 2003 was characterised by exceptionally warm weather in Europe with the average temperature exceeding that of any previous summer over the last 500 years. The seasonal 2003 summer temperature for central Europe was beyond the historical distribution range and could bear a closer resemblance with climate change scenarios for late XXI century. Nevertheless, it was the heatwave that occurred between the 1st and the 15th of August 2003 that had a major impact in excessive mortality rates througho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
177
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(190 citation statements)
references
References 13 publications
12
177
0
1
Order By: Relevance
“…In fact, the monthly SST, averaged over the entire Mediterranean Sea, for May, June, July and August 2003, were consistently above the corresponding monthly maximum values observed during the previous 45 years (Grazzini and Viterbo, 2003). Several authors have also identified a blocking regime over Europe (Beniston and Diaz, 2004;Trigo et al, 2005). Although the persistent SST warm values and the amplitude of the blocking event over Europe are likely to be closely linked, the exact role of high SST values within the sub-monthly or seasonal heatwave is still a matter of debate.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the monthly SST, averaged over the entire Mediterranean Sea, for May, June, July and August 2003, were consistently above the corresponding monthly maximum values observed during the previous 45 years (Grazzini and Viterbo, 2003). Several authors have also identified a blocking regime over Europe (Beniston and Diaz, 2004;Trigo et al, 2005). Although the persistent SST warm values and the amplitude of the blocking event over Europe are likely to be closely linked, the exact role of high SST values within the sub-monthly or seasonal heatwave is still a matter of debate.…”
Section: Discussionmentioning
confidence: 99%
“…These heatwaves were responsible for a significant increase of human mortality, unusually large fires and widespread impacts in ecosystems and crop yields (Trigo et al, 2005;García-Herrera et al, 2010;Barriopedro et al, 2011).…”
Section: A Bastos Et Al: Impacts Of 2003 and 2010 Heatwaves In Planmentioning
confidence: 99%
“…In large sectors of France and the Iberian Peninsula, daily maximum temperatures were between 7.5 • C and 12.5 • C above the 1961-1990 average for several weeks (Luterbacher et al, 2004;Trigo et al, 2005;García-Herrera et al, 2010). According to several authors, this event was so extreme in central Europe that it fell completely outside the range of any extreme episodes observed before, even for stations with more than 100 years of daily data (Schär et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Ogi et al (2005) pointed out that a strongly positive summertime AO is associated with occurrences of blocking anticyclones, which contributed to the abnormally hot European summer. Trigo et al (2005) also reported that a blocking anticyclone caused the anomalous hot summer of 2003. The blocking anticyclone over Europe in summer 2003 was shown to be part of a planetary-scale wave train, extending from Europe to eastern Eurasia (Orsolini and Nikulin 2006).…”
Section: Introductionmentioning
confidence: 99%